2000
DOI: 10.1128/iai.68.8.4399-4406.2000
|View full text |Cite
|
Sign up to set email alerts
|

Central Role of Endogenous Gamma Interferon in Protective Immunity against Blood-StagePlasmodium chabaudiAS Infection

Abstract: The role of endogenous gamma interferon (IFN-␥) in protective immunity against blood-stage Plasmodium chabaudi AS malaria was studied using IFN-␥ gene knockout (GKO) and wild-type (WT) C57BL/6 mice. Following infection with 10 6 parasitized erythrocytes, GKO mice developed significantly higher parasitemia during acute infection than WT mice and had severe mortality. In infected GKO mice, production of interleukin 12 (IL-12) p70 and tumor necrosis factor alpha in vivo and IL-12 p70 in vitro by splenic macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
263
6
8

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(294 citation statements)
references
References 46 publications
17
263
6
8
Order By: Relevance
“…26 Evidence indicates that IL-4, but not IL-13, acts via a STAT6-dependent mechanism to induce IFN-γ production by natural killer cells and natural killer T cells; 44 IL-4-induced IFN-γ production has been demonstrated in mice infected with Candida albicans and Leishmania major. 45,46 As observed in STAT6 -/-mice, IL-4 neutralization in P. chabaudi-infected WT mice resulted in a similar course of anemia despite a significantly higher peak parasitemia compared to that in isotype control WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Evidence indicates that IL-4, but not IL-13, acts via a STAT6-dependent mechanism to induce IFN-γ production by natural killer cells and natural killer T cells; 44 IL-4-induced IFN-γ production has been demonstrated in mice infected with Candida albicans and Leishmania major. 45,46 As observed in STAT6 -/-mice, IL-4 neutralization in P. chabaudi-infected WT mice resulted in a similar course of anemia despite a significantly higher peak parasitemia compared to that in isotype control WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…26 IL-13 levels were determined using a DuoSet ELISA kit (R&D Systems, Minneapolis, MN, USA) according to the manufacturer's instructions.…”
Section: Cytokine Quantificationmentioning
confidence: 99%
“…IFN-g is a pro-inflammatory cytokine that is intimately involved in the innate and acquired immune responses. This cytokine has important roles in immunity against blood-stage malaria, because a previous study has demonstrated that IFN-g KO mice are highly susceptible to infection with Plasmodium chabaudi AS-pRBC [20]. First, the irradiated recipients transferred with CD8 1 T cells from immune mice were treated with neutralizing antibodies to IFN-g prior to infection with PyL.…”
Section: Ifn-c From Cd8 1 T Cells Is Important To Protect Against Infmentioning
confidence: 99%
“…Numerous studies have revealed the importance of the cytokine balance in immune protection against malaria. A Th1/pro-inflammatory cytokine (IFN-γ, IL-12 and TNF-α) response during the early stage of infection mediates protective immunity and the resolution of parasite infection (1)(2)(3)(4)(5)(6). The initial pro-inflammatory response may switch to a predominant anti-inflammatory response that is mediated by immunoregulatory cytokines, such as TGF-β and IL-10 which down-regulate proinflammatory cytokine production to avoid malaria-associated pathology (7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%